Kvantitativ analyse av forvitringsmateriale og kvartærgeologisk kartlegging av Hadseløya, Vesterålen, Nord-Norge. - implikasjoner for isutbredelsen i Weichsel - Strømsøe, Jørund Raukleiv (The University of Bergen, 2005)
“A quantitative analysis of weathered material and a geomorphological mapping ofHadseløya, Vesterålen, Northern Norway. – Implications for the Weichselian ice sheet extension” Hadseløya (102 km2) is the southernmost island (position 68° 30´N 15°E) in the Vesterålen archipelago located in Northern Norway constituting the study area for this thesis. The island is characterized by low-relief surfaces containing various kinds of weathering material, and a dissected landscape covered by glacial, periglacial and colluvial deposits and landforms. The spatial distribution of superficial deposits and landforms in the study area has previously received modest attention, and has been subject for only large-scale mapping. Still, some of these features have been applied in reconstructions of the Weichselian ice sheet configuration, and the Late-Weichselian deglaciation history of the region. With the aim of obtaining a better understanding of the physical properties of weathered material, a comprehensive analysis of the regolith has been carried out within a geomorphological context. The results are discussed against possible ice sheet scenarios. By combining XRD-analysis, grain-size distribution and geomorphological mapping,sedimentary characteristics of various weathered material has been documented, in addition to the spatial distribution of landforms. Five pits were excavated and logged in detail. Four of them are located on plateaus made up of in situ weathered material, whereas the fifth was located in a fluvial downcutting. All pits reveal either pedolithic material, saprolite structures or a combination of these. No glacigenic material was observed in the profiles. In the porous saprolite, which occasionally show corestones, original bedrock structures are preserved. In order to complement this approach an additional 14 localities were sampled (n=32). The pits were sampled at different depths for the purpose of analyzing both the vertical grain-size distribution and the mineralogical properties of the clay and silt ...